FAKTOR – FAKTOR YANG MEMPENGARUHI TINGGINYA KASUS KARIES GIGI PADA ANAK PANTI ASUHAN YATAAMA AL-FIRDAUSI DI WILAYAH KERJA PUSKESMAS NGESREP TAHUN 2011 - Jannyta Joséphin Nelwan (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Caries is a disease of the hard tissues of the tooth, namely email, dentin and pulp are fermented, the sign is the demineralization of dental hard tissue which is then followed by the breakdown of organic matter resulting in infasi bacteria and dead pulp and periapical kejaringan spread of infection that can cause pain (Kidd , 1991).What factors are affecting the high incidence of dental caries in children orphanage Yataama Al Firdaus and seeks to improve health in the form of activity with the approach of promotive, preventive, curative, which is implemented in an integrated, holistic, and sustainable.To determine the factors - Factors Affecting Higher Case Dental Caries in Children Orphanage In the PHC Ngesrep Work in 2011.Objective: Knowing the incidence of caries figures DMF-T and def-t, the level of knowledge, attitudes and behavior towards dental health and an action plan Knowing promotive, preventive and curative simple to be performed on children orphanage Yataama Al FerdowsiDescriptive survey research methods to perform data retrieval Yataama In Children Orphanage Al-Ferdowsi In the region of Puskesmas Ngesrep, to see cases of caries and the factors that influence the high incidence of dental caries seen from the health status and oral hygiene by way of examination in children and the administration of the questionnaire. In children deciduous teeth caries was found that about 1 - 5 teeth in 39 children, or by 36.11%. Still finding of caries in primary teeth show that there are factors that lower knowledge about dental health lower resulting in the occurrence of dental caries.Permanent dental caries is widely found in damages 1 - 5 teeth by 67 children or 62%. This incident shows that the high status of dental caries in children orphanage Al-Firdaus as a result of the low level of knowledge on dental health of children.The low level of knowledge, behavior and attitude of the orphanage on the health of the teeth and mouth can be seen from the data processing through questionnaires given in the orphanage.